Literature Review : Dampak Gadget terhadap Kesehatan Fisik dan Mental Anak - Nurbaiti Nurbaiti; Nasmi Nasmi; Marniati Marniati (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Advances in digital technology have brought major changes in human life, including in communication behavior and daily activities. Gadgets such as smartphones, tablets, and laptops are now widely used, including by children and teenagers. However, uncontrolled use of gadgets has a negative impact on physical and mental health. This study aims to examine various diseases and health problems that arise due to the use of gadgets in children and adolescents, through the analysis of ten scientific articles. The results of the study showed various symptoms and disorders including headaches, visual impairments, obesity, stress, anxiety, insomnia, as well as concentration and emotional disorders. Lack of parental supervision, lack of digital literacy, and unfettered access to digital content exacerbate this impact. Prevention through active involvement of family and school, education on healthy use, and time management are important steps in minimizing health risks due to gadgets.